2020
DOI: 10.1101/2020.10.27.357558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike D614G variant confers enhanced replication and transmissibility

Abstract: During the evolution of SARS-CoV-2 in humans a D614G substitution in the spike (S) protein emerged and became the predominant circulating variant (S-614G) of the COVID-19 pandemic. However, whether the increasing prevalence of the S-614G variant represents a fitness advantage that improves replication and/or transmission in humans or is merely due to founder effects remains elusive. Here, we generated isogenic SARS-CoV-2 variants and demonstrate that the S-614G variant has (i) enhanced binding to human ACE2, (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 29 publications
6
82
0
Order By: Relevance
“…Improved stability may be the reason why SARS-CoV-2-S D614 was superseded by the S G614 variant within a few months of circulation in humans (43). Animal studies showed that the SARS-CoV-2-S G614 variant has higher fitness and transmissibility (40)(41)(42). This is reminiscent of influenza virus, for which the link between hemagglutinin stability and transmissibility is well established (13,68).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved stability may be the reason why SARS-CoV-2-S D614 was superseded by the S G614 variant within a few months of circulation in humans (43). Animal studies showed that the SARS-CoV-2-S G614 variant has higher fitness and transmissibility (40)(41)(42). This is reminiscent of influenza virus, for which the link between hemagglutinin stability and transmissibility is well established (13,68).…”
Section: Discussionmentioning
confidence: 99%
“…Within a few months circulation among humans, SARS-CoV-2 has acquired a mutation (D614G) in its spike protein, that is increasingly recognized as a possible cause of enhanced virus transmission (40)(41)(42). The D614G mutation was already detected during the early phase of the pandemic and, after four months, the S G614 variant became globally predominant (43).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper bounds of the dose–response curve are consistent with the infectivity of two different variants of SARS-CoV-2 in mice, hamsters, and ferrets, which showed 100% infectivity at a dose of 10 5 TCID 50 . 46 Monte Carlo simulations were used to incorporate the uncertainty and variability of the input parameters. The model was simulated 50,000 times.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous reports focused on the spike D614G variation (Díez-Fuertes et al, 2020;Korber et al, 2020;Plante et al, 2020;Zhou et al, 2020). Although it is not the most frequent variation, it is quite prevalent, and its occurrence in the spike protein made it an attractive target for speculations about an effect on viral transmissibility, infection efficiency, virulence, immunogenicity, immune evasion, and even disease prognosis (Grubaugh et al, 2020;Hou et al, 2020;Korber et al, 2020;Zhou et al, 2020). Yet, the only solid experimental evidence supports a slightly higher transmissibility but no significant structural effects leading to virulence or immune evasion (Díez-Fuertes et al, 2020;Grubaugh et al, 2020;Korber et al, 2020;Plante et al, 2020).…”
Section: Discussionmentioning
confidence: 99%